IJRTP Volume 12(iii) Editorial / Introduction (The international journal of religious tourism and pilgrimage, 2024)
Editorial / Introduction to Special Issue derived from Papers Presented at International Conference on Religious Tourism (ICRT-2023), held at the Department of Management Studies, Babasaheb Bhimrao Ambedkar University Lucknow, (U.P), India, 27-28 March 2023